Pemberian Tepung Tempe Meningkatkan Kualitas Tulang pada Tikus Ovariektomi (ADMINISTRATION OF TEMPE FLOUR IMPROVING THE QUALITY OF OVARIECTOMY-RATS BONE) - Suarsana, I Nyoman; Silitonga, Samuel Leonardo; Dharmawan, I Nyoman Sadra; Kardena, I Made; Priosoeryanto, Bambang Pontjo (Jurnal Veteriner; Vol 15 No 4 (2014), 2015)
Study to determine the potential of tempe flour in improving bone quality of ovariectomized rats (ovx)based on calcium (Ca) and phosphorus(P) levels in the plasma and bones; osteoblast and osteoclastprofiles have been conducted for 4 months. A total of 20 female Sprague Dawley albino rats, age of 3months and average body weight of 200 g were used in this study. The rats were divided into 4 groups,i.e.normal rats + diets (K0); normal rats +tempe flour (K1); ovx + diets (OV0); and ovx + tempe flour (OV1),respectively. The Ca and P levels in plasma and bones were analyzed using Atomic AbsorptionSpectrophotometer (AAS) and spectrophotometric methods. In addition, the profiles of osteoblast andosteoclast were also observed. The results showed that Ca and P levels in plasma and bones of normal ratswere 11.08 mg/dL and 7.06 mg/dL; 30.88 mg/dL and 18.63 mg/dL, respectively. The highest Ca and P levelsin both plasma and bones were observed in normal rats which were given tempe flour (K1), 11.25 mg/dLand 7.42 mg/dL; and 31.60 mg/dL and 19.78 mg/dL, respectively. Similarly, Ca and P levels in plasma andbones of ovxwhich were given tempe flour were slightly higher (10.91 mg/dL and 6.96 mg/dL; and 29.89 mg/dL and 17.87 mg/dL) compared to ovx without tempe flour diets (9.38 mg/dL and 6.46mg/dL; and 26.58 mg/dL and 16.75 mg/dL). The numbers of osteblast was found slightly higher both in normal rats and ovxwhich were given tempe flour; whereas slightly decreased of osteoclast was observed only in ovx which weregiven tempe flour. The administration of tempe flour in ovx diets could improved bone quality as indicatedby the Ca and P levels in plasma and bones and decreased numbers of osteoclast.
Keywords: tempe flour, ovariectomized-rat, osteoclast